Evaluation of the distribution of activation inside a compact medical cyclotron. (June 2017) - Fujibuchi, Toshioh; Toyoda, Takatoshi; Baba, Shingo; Umezu, Yoshiyuki; Komiya, Isao; Sasaki, Masayuki; Honda, Hiroshi
Abstract: The distribution of activation inside a compact medical cyclotron was evaluated by measuring 1 cm dose equivalent rates and γ-ray spectra. Analysis of the distribution of activation showed high activation at the deflector and the magnetic channel. Radionuclides 60 Co, 57 Co, 65 Zn, and 54 Mn were detected. Different radionuclides were generated from different components of the cyclotron, and low-activity radionuclides could be detected under low-background-radiation conditions. Highlights: The distribution of activation inside a compact medical cyclotron was evaluated. Activation was high at the deflector and the magnetic channel. 60 Co, 57 Co, 65 Zn, and 54 Mn were detected by γ-ray spectrometry.